Millenial Mothers’ Digital Literacy regarding Child Disease and Health Issues - Fauziati, Choirunnisak (UI Scholars Hub, 2021)
It is important for millennial mothers to have digital literacy. Millenials are known to have a tight relationship with digital media. Rather than fathers, mothers more often look for any information on child health issues. The study aimed to dig around mothers’ digital literacy practice which they did to obtain information from various online media, and also further understand the mothers’ comprehension on child disease and health issues. This qualitative research applied the post-positivitist paradigm with digital ethnographic method. The study suggests that Gilster’s (1997) digital literacy phases may be added by information sharing phase. This research also added understanding that there was a skill level gradation in each phase, in which the respective phase consisted of low, medium, and high levels. In addition, the mothers’ digital literacy were more affected by interests, curiosities, and needs. It was not always directly proportional to the issue literacy skill. On the other hand, millennial mothers’ online media choices were also affected by the convenience and benefit perceptions of such media. The research also found 5 (five) child disease and health issues which became the millennial mothers’ concerns, namely: 1) common disease, 2) accident, 3) emergency, 4) mental health, and 5) COVID-19 pandemic. It also showed that an interpretation of a disease affected the behaviour toward such disease. In addition, the interpretation was inclined to be affected by the social construction in the media. However, if we observed this from the active audience perspective, the millennial mothers who choose to limit exposures to information on a disease will behave differently from those who do not limit their exposures to information.